(untitled) (Journal of Forensic Medicine & Toxicology, 2022)
Background: The wrinkles and grooves on the labial mucosa (called sulci labiorum) form a characteristic pattern which is known as lip print. The study of these lip print is called cheiloscopy. Lip prints are considered unique to an individual and analogous to fingerprints. Aim & Objectives: -To observe the various lip print patterns in the study population. To estimate the prevalence of lip print pattern, quadrant wise. To evaluate the gender differences in the lip print pattern. Materials & Methods: It’s an observational study, conducted among healthy male and female students of 18 – 25 years of a tertiary care centre in South India.